(untitled) (Biological Sciences - PJSIR, 2003)
A simple and economical procedure for the large-scale extraction of silymarin from the dried seeds of Silybum marianum has been developed. After harvest the cellular and acellular constituents of the seeds are biodegradable. Using the fresh seeds, a viable procedure has been perfected for the extraction of silymarin (yield 1.47 %). The product appeared as a mixture and was resolved into the isomers by centrifugal chromatography. The identity of the product and its isomers were confirmed through comparison with standards using mp, UV, IR, 1H NMR and Mass spectrometric data and 2,4, dinitrophenylhydrazone assay.